Simultaneous Removal Of Ammonium And Phosphate Using Magnesium Chloride Modified Zeolite - Gunasegran, Vikneshan (Universiti Sains Malaysia, 2021)
This study analyzed individual and simultaneous sorption of ammonium (NH4+) and phosphate (PO43-) and their mechanisms together with their major operating parameters such as initial nutrient concentration, types of zeolites, and addition of salt onto Mg2+-modified zeolites. The phosphate reported a removal efficiency of -62.68% due to poor sorption for individual sorption, and 13.49% for simultaneous removal. Besides, the removal efficiency of ammonium in individual and simultaneous sorption is 59.98% and 35.87%, respectively. The ammonium and phosphate removal efficiency decreases as the initial nutrient concentration increases. Moreover, the mordenite typed zeolites showed much better adsorption for both individual and simultaneous with a higher removal efficiency of 59.98% and 35.87%, respectively for ammonium at an initial concentration of 20 ppm. However, the zeolite-Y had more adsorption capacity towards phosphate with a higher removal efficiency of 19.91%. The individual presence of Na+ had a significantly negative effect on the removal of ammonium as Na+ possesses small ionic radii than NH4+, which reduces ammonium uptakes. The pseudo-second-order model could describe the adsorption of nutrients with higher (R2 ≥ 0.99), where chemical actions mainly govern the process. The Langmuir model can be acceptably applied to fit the experimental data with a higher correlation coefficient (R2 = 0.995) for individual ammonium sorption, suggesting that the adsorption is a monolayer coverage. The addition of MgCl2 to the reaction system promoting the desorption process for both separate and simultaneous processes revealed the possibility of regeneration and reusability of the adsorbent.